Character Education Transformation: Awakening the Role of Ulama through the Ulama Cadre Student Standard Program - Ahmadi Fathul Wahab; M. Samsul Hady; Mohammad Samsul Ulum (Al-Qalam Institute, 2024)
This research focuses on the effectiveness of the Ulama Cadre Student Standards (SSKU) program in shaping the character of students at Madrasah Aliyah Almaarif Singosari. The research method used is qualitative research with a descriptive approach, which involves in-depth interviews, observations, and the collection of documents related to the SSKU program. Through data analysis conducted using Miles and Huberman interactive techniques, the study found that the SSKU program successfully instilled religious and social values in students. A thorough evaluation showed that students' involvement in religious activities increased, and they actively led social events such as tahlil and yasin. Students also report increased self-confidence and social skills, signaling the program's positive impact on the formation of the character of the clerics. The implications of this study emphasize the importance of integration between theory, practice, and example in religious education, which can be used as a model for other educational institutions that want to develop students' character through a scholar-based approach. Thus, this research is expected to contribute to the development of character education policies in the context of Islamic education in Indonesia.